Program Keselamatan dan Kesehatan Kerja di Atas Kapal (Meningkatkan Keamanan Awak Kapal) - Sakina Sumantri; Susilawati S (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Occupational safety and health has been a concern on the part of government and business for a long time. The safety factor is very important because it is closely related to employee performance and company performance. The purpose of this study is to explain the safety and health program on board and the security of the crew as a part of management. In occupational safety and health programs, namely: counseling, training, health checks, personal protective equipment (PPE) and supervision programs. The research method used is the analysis of counseling and training articles conducted to increase knowledge about OSH. Increasing knowledge and skills is achieved by counseling and training. Improving the knowledge and skills of the crew is the main goal in the training and counseling program.